Structure Inversion Asymmetry and Rashba Effect in Quantum Confined Topological Crystalline Insulator Heterostructures. (29th March 2021) - Rechciński, Rafał; Galicka, Marta; Simma, Mathias; Volobuev, Valentine V.; Caha, Ondřej; Sánchez‐Barriga, Jaime; Mandal, Partha S.; Golias, Evangelos; Varykhalov, Andrei; Rader, Oliver; Bauer, Günther; Kacman, Perła; et al.
Abstract: Structure inversion asymmetry is an inherent feature of quantum confined heterostructures with non‐equivalent interfaces. It leads to a spin splitting of the electron states and strongly affects the electronic band structure. The effect is particularly large in topological insulators because the topological surface states are extremely sensitive to the interfaces. Here, the first experimental observation and theoretical explication of this effect are reported for topological crystalline insulator quantum wells made of Pb1− x Sn x Se confined by Pb1− y Eu y Se barriers on one side and by vacuum on the other. This provides a well defined structure asymmetry controlled by the surface condition. The electronic structure is mapped out by angle‐resolved photoemission spectroscopy and tight binding calculations, evidencing that the spin splitting decisively depends on hybridization and, thus, quantum well width. Most importantly, the topological boundary states are not only split in energy but also separated in space—unlike conventional Rashba bands that are splitted only in momentum. The splitting can be strongly enhanced to very large values by control of the surface termination due to the charge imbalance at the polar quantum well surface. The findings thus, open up a wide parameter space for tuning of such systems for device applications. Abstract : Structure inversion asymmetry in topological crystalline insulator quantum well heterostructures is unraveled by angle‐resolved photoemission spectroscopy and tight binding calculations. Large splittings of topological states in energy and momentum are observed, in strong dependence of hybridization and quantum well thickness. This splitting can be enhanced to very high values by control of the surface termination.